Fishy Tech: Netting E-Fishery's Billion-Dollar Fraud through Pentagon Theory Analysis - Andrew, Andrew; Nariman, Augustpaosa (Jurusan Akuntansi Politeknik Negeri Malang, 2025)
Purpose: The causal mechanisms behind startup fraud in Indonesia by analyzing the E-Fishery case through the lens of the Fraud Pentagon Theory. Method: Qualitative methodology combining systematic literature review and case study analysis. Results: E-Fishery systematically inflated revenue by up to 4.8 times actual figures through dual record-keeping systems, nominee companies, and coordinated organizational deception. Novelty: The first systematic application of Pentagon Theory to analyze startup fraud in emerging market contexts, revealing how the five elements interact synergistically. Contribution: Developing enhanced fraud detection and prevention strategies in Indonesia's venture-backed startup ecosystem. Abstrak: Fishy Tech: Netting E-Fishery's Billion-Dollar Fraud Through Pentagon Theory Analysis Tujuan: Menganalisis mekanisme kausal di balik penipuan startup di Indonesia melalui pengkajian kasus E-Fishery menggunakan kerangka Teori Fraud Pentagon. Metode: Metodologi kualitatif yang mengombinasikan tinjauan pustaka sistematis dan analisis studi kasus. Hasil: E-Fishery secara sistematis menggembungkan pendapatan hingga 4,8 kali dari angka sebenarnya melalui sistem pembukuan ganda, perusahaan nominee, dan penipuan organisasional terkoordinasi. Kebaruan: Aplikasi sistematis pertama Teori Pentagon untuk menganalisis penipuan startup dalam konteks pasar berkembang dan mengungkap bagaimana kelima elemen berinteraksi secara sinergis. Kontribusi: Mengembangkan strategi deteksi dan pencegahan penipuan yang lebih baik dalam ekosistem startup Indonesia yang didukung modal ventura.